Association Between Serum 25-OH-Vitamin D and Diabetic Foot Ulcer in Patients With Type 2 Diabetes - Jiezhi Dai (Frontiers in Nutrition, 2020)
Background: Vitamin D deficiency has been associated with an increased risk in several diabetic complications. We aimed to evaluate the association between vitamin D and diabetic foot ulcer (DFU) in patients with type 2 diabetes.Methods: Fifty one patients were included in the study and divided into two groups for study of vitamin D, cholesterol, and triglycerides in blood serum on DFU. The association between vitamin D and DFU was measured by binary logistic regression analysis. The cut point of vitamin D for DFU was assessed by the receiver operating characteristic curve.Results: Levels of 25-OH-vitamin D were lower in patients with DFU than in DM group (P < 0.0001). The AUC of 25-OH-vitamin D was 0.8254 and had an optimal cut point value (13.68 ng/ml) for the identification of DFU, with a sensitivity of 90% and a specificity of 66.67% in all patients. Multivariate logistic regression analysis indicated that the significant risk factors included 25-OH-vitamin D level (P = 0.001, OR = 0.618) and HDL-C level (P = 0.038, OR = 0.012).Conclusion: Low serum 25-OH-vitamin D level was associated with DFU. This indication was more specific than cholesterol and triglycerides levels.